Fraud Triangle Mendeteksi Kecurangan Dalam Laporan Keuangan Dana Desa - Kristanti Rahman; Rahayu Anggraeni; Dania Febriana (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
This study aims to test the Fraud Triangle to detect fraudulent financial reports of village funds with variables Morality (X1), Village Apparatus Competence (X2) and Compensation Suitability (X3) affecting Village Fund Fraud Prevention (Y) in Cilacap Regency. The sample in this study were 16 villages with 3 village officials per village, so that the total number was 48 people with Purposive sampling technique which was used as a research sample. Data analysis techniques with multiple linear regression using SPSS for Windows version 27.00.The results of this study indicate that Morality has no effect on Preventing Village Fund Fraud in Cilacap Regency. The competence of the Village Apparatus affects the Prevention of Village Fund Fraud in Cilacap Regency. Compensation Suitability affects the Prevention of Village Fund Fraud in Cilacap Regency.